Island of Bewilderment : A Novel of Modern Iran - Dānishvar, Sīmīn, 1921-2012 (Book collections on Project MUSE., 2022)
"Set in Tehran in the mid-1970s, just a few years before the 1977-79 revolution, Daneshvar's unforgettable novel depicts the tumultuous social, cultural, and economic changes of the day through the intimate story of a young woman's struggle to find her identity"--